2012
DOI: 10.1155/2012/132056
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate Increases Skeletal Muscle GLUT4 Expression and Improves Metabolic Control in Experimental Diabetes

Abstract: Long-term administration of 5-aminoimidazole-4-carboxamide ribonucleoside (AICAR) mimics the effects of endurance exercise by activating AMP kinase and by increasing skeletal muscle expression of GLUT4 glucose transporter. AICAR is an intermediate in the purine de novo synthesis, and its tissue concentrations can be increased, in vivo, by low doses of methotrexate (MTX) through the inhibition of the enzyme AICAR transformylase. We report here the first evidence that, in experimental type 2 diabetes, chronic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…1) Another inhibitor of thymidylate synthase and AICART, pemetrexed, increases ZMP and activates AMPK 57 - 59 . In summary, experimental evidence in cell culture, animal experiments 30 and observations in patients support the view that methotrexate and related compounds can increase AICAR production and activate AMPK in addition to their inhibitory effects on nucleotide synthesis, which is still the claimed basis for immune-suppressive activity. Nevertheless, the molecular mechanisms underlying the “anti-inflammatory” activity and the postulated targets cells (T-lymphocytes in psoriasis, macrophages and monocytes in rheumatoid arthritis) are still not completely understood.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…1) Another inhibitor of thymidylate synthase and AICART, pemetrexed, increases ZMP and activates AMPK 57 - 59 . In summary, experimental evidence in cell culture, animal experiments 30 and observations in patients support the view that methotrexate and related compounds can increase AICAR production and activate AMPK in addition to their inhibitory effects on nucleotide synthesis, which is still the claimed basis for immune-suppressive activity. Nevertheless, the molecular mechanisms underlying the “anti-inflammatory” activity and the postulated targets cells (T-lymphocytes in psoriasis, macrophages and monocytes in rheumatoid arthritis) are still not completely understood.…”
Section: Resultsmentioning
confidence: 91%
“…Our concept, namely that part of the action of methotrexate is based on activation of AMPK via AICAR (ZMP), is supported by experiments with genetically diabetic (db + /db + ) mice, where glucose and insulin levels are significantly lowered after only 4 weekly i.p. methotrexate doses (0.5 mg/kg) 30 . Unfortunately, the authors failed to demonstrate that either AMPK or own of its downstream effectors such as acetyl-Coenzyme A -carboxylase were phosphorylated.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, cellular accumulation of AICAR directly activates AMPK. Consistent with this mechanism, methotrexate promotes glucose uptake and lipid oxidation in skeletal muscle, which is AMPK dependent, and reduces hyperglycemia in rodent models of T2D (146,150,151). Methotrexate has also been shown to inhibit atherogenesis in cholesterol-fed rabbits (152).…”
Section: Small-molecule Antiinflammatory Drugsmentioning
confidence: 79%
“…Russo et al . reported that the antifolate compound methotrexate (MTX), an inhibitor of dehydrofolate reductase , when administered at low doses to a mouse model of type 2 diabetes, inhibited the transformylase activity of ATIC, and caused an accumulation of ZMP, which activated AMPK and its downstream pathways, resulting in the activation of insulin‐independent GLUT4 expression in skeletal muscle . The increase in GLUT4 expression was associated with a marked decrease in both glucose and insulin serum levels, thus improving metabolic control in genetically diabetic mice.…”
Section: Enzymes Participating In Adenylate Metabolismmentioning
confidence: 99%
“…Although this conclusion appears to contradict all of the above reported results, there are several explanations for the profound differences on the effect of a decreased ATIC activity on AMPK activation. Whereas other research groups performed ex vivo experiments on cell lines of human origin [37,39,46,49], and in vivo experiments on a mammalian model [37,42], Stenesen et al [52] performed their in vivo experiments on an insect model. To the best of our knowledge, the extent to which the de novo pathway contributes to the biosynthesis of the adenylate pool relative to the salvage pathway in insects remains unknown.…”
Section: -Aminoimidazole-4-carboxamide Ribonucleotide Formyltransfermentioning
confidence: 99%